A Measurement of Budget Performance Which Is Influenced By Budget Participation, Work Motivation And Work Environment - Asyari; Krisnandi, Herry; Yolanda, Olivia (INTERNATIONAL JOURNAL OF ECONOMICS, MANAGEMENT, BUSINESS, AND SOCIAL SCIENCE (IJEMBIS), 2023)
The aim of this research is to determine and analyze the factors that influence the dependent variable (Y), work motivation (X1) work environment (X2), and budget participation (X3) on budget performance (Y) at the DKI Jakarta Regional Revenue Service. The analytical method used was quantitative descriptive analysis with multiple linear regression. The results of the analysis using SPSS (Statistical Program and Services Solution) version 21 showed that from the results of the regression coefficient Y = 1,216+0.259X1 + 0.525X2 +0.154X3, it showed that each independent variable provided an influence on improving budget performance. The R Square value (Coefficient of Determination) is 0.464. Test results simultaneous (F test) show that together the independent variables have a significant effect on budget performance in the DKI Jakarta Regional Revenue Service. The results of the partial test (T-test) show that the independent variables, namely work motivation, work environment, and budget participation have a significant effect on budget performance.